Ecophysiological characterization of a nitrite-oxidizing bacterial culture from a freshwater aquaculture pond. Issue 1 (4th November 2022) - Zhou, Runfeng; Li, Yayuan; Xiao, Shuwen; Liu, Xingguo; Liu, Chong; Cheng, Guofeng; Zhang, Wang; Lu, Shimin
Abstract: Nitrite is harmful to aquatic animals in freshwater pond aquaculture environments. Nitrite is oxidized to nitrate mainly by nitrite-oxidizing bacteria (NOB). NOB may be promising in the control of nitrite concentration in aquaculture water. To better understand the role of NOB in the nitrogen cycling process of freshwater aquaculture ponds, we describe the characterization of NOB by using a culture derived from a freshwater aquaculture pond. Analysis by 16S rRNA sequence alignment showed that the NOB in the culture belong to the genus Nitrospira, whose generation time and nitrite–oxidizing rate were 9.87 h and 4.63 (± 0.07) pg NO2 − –N cell −1 ·h −1 in the exponential growth phase, respectively. The oxidation of nitrite could be inhibited completely when the concentration of dissolved oxygen was 1.0 ± 0.5 mg/L. −1 The NOB could oxidize nitrite into nitrate at 29.84‰ salinity. However, the nitrification rate decreased significantly with an increase in salinity concentration ranging from 5.72‰ to 29.84‰. The optimal temperature range was 25–37 °C for the growth of NOB, and activity significantly decreased when the temperature was below 20 °C or reached 40 °C. In this study, the initial pH 6 ± 0.1–8 ± 0.1 was not observed to affect the nitrification activity of the NOB culture. Illumination of 410 ± 10 nm can completely inhibit NOB nitrification, and 520 ± 10 nm illumination partially inhibits NOB, whereas 660 ± 10 nm illumination has no effect. These findings indicate that the degree of photoinhibition in NOB increases with decreasing wavelength.